Situation Report: Hungary, 18 May 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Lackluster HSWP CC Meting / by Alfred Reisch CC Secretary Matyas Szuros' Visit the USA / by Edith Markos Unpublished Economic Report Proposes New Reform / by Karoly Okolicsanyi Bankruptcy: The First Company Goes Under / by Karoly Okolicsanyi Official Seeks Church Cooperation on Social, Minority Issues / by Edith Markos Minority Issue: Hungary Rebuts Romanian Charges / by Alfred Reisch The HSWP and the Writers' Union Reach a Compromise / by Judith Pataki Political Conscientious Objector Sentenced / by Judith Pataki